Komunitas Kelelawar (Ordo Chiroptera) di Beberapa Gua Karst Gunung Kendeng Kabupaten Pati Jawa Tengah - Tamasuki, Kamal; Wijayanti, Fahma; Fitriana, Narti (Al-Kauniyah: Jurnal Biologi, 2015)
The existance of bats in cave type with diverge managerial system are influenced abundance and species bats. This research was conducted from January to June 2012 that counting abundance and to identify bats at Gunung Kendeng Karst Area Pati Central Java. The bats were collected by using mist net and stalk net at flying track surrounding cave’s mouth of Pancur Cave, Serut Cave, Bandung Cave, Pawon Cave, Larangan Cave and Gantung Cave. Bats abundance at Pancur Cave amount  ±  484 bats, Serut Cave amount ± 1233 bats, Bandung Cave amount ± 715 bats, Pawon Cave amount ± 392 bats, Larangan Cave ± 23 bats and Gantung Cave ± 5 bats. The six species were collected from this research, such as Cyanopterus horsfieldii, Hipposederos larvatus, Hipposideros bicolor, Rhinolophus affinis, Murina suilla dan Miniopterus australis. The analyst result is used Diversity Index of Shannon-Wiennner showed the highest diversity at Pancur Cave (H=0,35054) and the lowest at Gantung Cave (H=0,13633). Similarity index of shannon Evenness is showed the highest similarity at Pancur Cave (E=0,50572) and the lowest at Larangan Cave (E=0). Domination index of simpson is showed the highest domination at Pancur Cave (C=0,06805)  and the lowest at Gantung Cave (C=0,00189). Hipposederos larvatus and Miniopterus australis are species that common and often founded during this research.